Chondroblastic Osteosarcoma: A Review - K. Kiran Kumar Patro (Indian Journal of Forensic Medicine & Toxicology, 2020)
The main purpose of this article to present a review on chondroblastic osteosarcomaand its prevalencein the different jawbones of the body. The word osteosarcoma mainly refers to a group of heterogeneousmalignancies that involves bone formation or it can also results due to mesenchymal tissue with evidenceof osteogenic disparity. It has been reported around 25% of the pattern of the chondroblastic osteosarcomasrepresents neoplasms.